Percutaneous vertebroplasty and percutaneous balloon kyphoplasty for the treatment of osteoporotic vertebral fractures: a systematic review and cost-effectiveness analysis - Matt Stevenson; Tim Gomersall; Myfanwy Lloyd Jones; Andrew Rawdin; Monica Hernández; Sofia Dias; David Wilson; Angie Rees (Health Technology Assessment, 2014)
Background: Percutaneous vertebroplasty (PVP) is a minimally invasive surgical procedure in which bone cement is injected into a fractured vertebra. Percutaneous balloon kyphoplasty (BKP) is a variation of this approach, in which an inflatable balloon tamp is placed in the collapsed vertebra prior to cement injection. Objectives: To systematically evaluate and appraise the clinical effectiveness and cost-effectiveness of PVP and percutaneous BKP in reducing pain and disability in people with osteoporotic vertebral compression fractures (VCFs) in England and Wales. Data sources: A systematic review was carried out. Ten databases including MEDLINE and CINAHL were searched from inception to November 2011, and supplemented by hand-searching relevant articles and contact with an expert. Studies met the inclusion criteria if they were randomised controlled trials (RCTs) including people with painful osteoporotic VCFs with a group receiving PVP or BKP. In addition, lead authors of identified RCTs were contacted for unpublished data. Review methods: Primary outcomes were health-related quality of life; back-specific functional status/mobility; pain/analgesic use; vertebral body height and angular deformity; incidence of new vertebral fractures and progression of treated fracture. A manufacturer provided academic-in-confidence observational data indicating that vertebral augmentation may be associated with a beneficial mortality effect, and that, potentially, BKP was more efficacious than PVP. These data were formally critiqued. A mathematical model was constructed to explore the cost-effectiveness of BKP, PVP and operative placebo with local anaesthesia (OPLA) compared with optimal pain management (OPM). Six scenario analyses were conducted that assessed combinations of assumptions on mortality (differential beneficial effects for BKP and PVP; equal beneficial effects for BKP and PVP; and no effect assumed) and derivation of utility data (either mapped from visual analogue scale pain score data produced by a network meta-analysis or using direct European Quality of Life-5 Dimensions data from the trials). Extensive sensitivity analyses were conducted on each of the six scenarios. This report contains reference to confidential information provided as part of the National Institute for Health and Care Excellence appraisal process. This information has been removed from the report and the results, discussions and conclusions of the report do not include the confidential information. These sections are clearly marked in the report. Results: A total of nine RCTs were identified and included in the review of clinical effectiveness. This body of literature was of variable quality, with the two double-blind, OPLA-controlled trials being at the least risk of bias. The most significant methodological issue among the remaining trials was lack of blinding for both study participants and outcome assessors. Broadly speaking, the literature suggests that both PVP and BKP provide substantially greater benefits than OPM in open-label trials. However, in double-blinded trials PVP was shown to have no more benefit than local anaesthetic; no trials of BKP compared with local anaesthesia have been conducted. A formal analysis of observational mortality data undertaken within this report concluded that it was not possible to say with certainty if there is a difference in mortality between patients undergoing BKP and PVP compared with OPM. Results from the cost-effectiveness analyses were varied, with all of BKP, PVP and OPLA appearing the most cost-effective treatment dependent on the assumptions made regarding mortality effects, utility, hospitalisation costs and OPLA costs. Limitations: Data on key parameters were uncertain and/or potentially confounded, making definitive conclusions difficult to make. Conclusion: For people with painful osteoporotic VCFs refractory to analgesic treatment, PVP and BKP perform significantly better in unblinded trials than OPM in terms of improving quality of life and reducing pain and disability. However, there is as yet no convincing evidence that either procedure performs better than OPLA. The uncertainty in the evidence base means that no definitive conclusion on the cost-effectiveness of PVP or BKP can be provided. Further research should focus on establishing whether or not BKP and PVP have a mortality advantage compared with OPLA and on whether or not these provide any utility gain compared with OPLA. Study registration: This study was registered as PROSPERO number CRD42011001822. Funding: The National Institute for Health Research Health Technology Assessment programme.